Teaching Philosophy: Instilling Pious Wonder or Vicious Curiosity? - Merrick, Teri (Christian scholar's review, 2010)
In this essay Teri Merrick argues that Christian philosophers are uniquely called to cultivate a disposition of wonder in their students, despite its strong family resemblance to the medieval vice of curiosity (curiositas). The argument hinges on showing that wonder is essential tothe practice of authentic Christian hospitality. Wonder is claimed to be the emotional marker designating the potentially subversive and existentially risky nature of this practice. She ends by exploring how philosophy instructors can promote a properly pious sense of wonder towards creatures and the ongoing creational work of God without simultaneously encouraging a vicious curiosity.